Endophytic Fungi Associated with the Medicinally important Aromatic plant Artemisia nilagirica (Clarke) Pamp. and Antimicrobial activity of selected Endophytic Fungi against Rhizoctonia solani - Parismita, Sarma; Manoj, Kumar; S, Dkhar Mamtaj; Highland, Kayang; Ruth, Laldinthar; K, Dubey Nawal; Richa, Raghuwanshi (Asian Journal of Biological and Life Sciences, 2016)
Endophytic fungi associated with the medicinally important aromatic plant Artemisia nilagirica (Clarke) Pamp. were isolated following the method of Suryanaryanan et al. [1]. The colonization frequency (% CF) of each endophytic fungal species was calculated following the method of Hata and Futai (1995). The highest colonization frequency in the leaf of A. nilagirica was exhibited by Phoma eupyrena (17.36%), and Tichoderma viride exhibited highest colonization frequency in the stem (14.58%) and root (15.28%) each. The Shannon- Weiner’s diversity index ranged from 2.6- 2.8 and Simpson’s diversity index ranged from 0.8- 1. The method of Skidmore and Dickinson [2] was followed for antimicrobial activity of selected endophytic fungi against Rhizoctonia solani. Altogether, 45 endophytic fungi belonging to 25 genera were isolated from the leaf, stem and root of A. nilagirica, of which 25 from leaf, 20 from stem and 24 from root. Among the isolates, seven endophytic fungi Acremonium cerealis, Aspergillus fumigatus, Cladosporium cladosporioides, Penicillium chrysogenum, Phoma eupyrena, Pythium irregulare and Trichoderma viride were selected to study the antimicrobial activities against Rhizoctonia solani. T. viride(62.5 %) was found to have the highest percentage inhibition, followed by P. irregulare (58.75 %), Acremonium cerealis (57.77 %), P. chrysogenum (55.55 %) and A. fumigatus (49.3 %). C. cladosporioides and P. eupyrena did not show any inhibition. From the present investigation, out of the seven fungal isolates, only five isolates showed inhibitory efficacy against the pathogen R. solani, the causal organism of root rot and damping off of seedlings in many economically important plants.
Keywords: Antimicrobial activity; Artemisia nilagirica; Endophytic fungi Rhizoctonia solani